Sistem Penghantaran Obat dengan Misel Polimer - Alasen Sembiring Milala (PT Dexa Medica, 2022)
Today is the era of nanotechnology, where almost all fields use nanotechnology. Likewise, the field of pharmaceutical technology is currently intensively developing pharmaceutical preparations using nanosystem. One of these nanosystems is polymeric micelles, which generally have particle size below 100 nm. Research showed that polymeric micelles have been proven to increase the solubility and bioavailability of hydrophobic drugs. There are several methods that can be used in polymeric micelles preparation, each of which has advantages and disadvantages. In order to characterize polymer micelles, parameter evaluation includes determination of critical micelle concentration (CMC), particle size, surface characteristics, stability, and release tests. Although most of the research on polymer micelles was applied in the field of oncology by the intravenous route of administration, researchers are currently developing drug delivery system using polymer micelles for oral route of administration. It can be further expected to initiate clinical research like such that has been done on intravenous administration.